BIOINFORMATICS EVALUATION OF CRISP2 GENE SNPs AND THEIR IMPACTS ON PROTEIN - Zaid A. Hussein; Abdulkareem A. Al-Kazaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study evaluated the CRISP2 gene’s functional single nucleotide polymorphisms, and its results may be advantageous for future population-based studies and early diagnostic discoveries, particularly in developing effective treatments. The CRISP2 gene encodes a secretory protein with a high cysteine content, which belongs to the family of cysteine-rich secretory proteins (CRISP). SNPs are genetic variations that may affect a protein’s structure or functionality. Prior to carrying out a broader population investigation, it is possible to evaluate suspected functional SNPs since it is challenging to uncover functional SNPs in disease-linked genes. As a result, using various bioinformatic prediction models, the potentially harmful three SNPs of the CRISP2 gene were predicted in this in-silico study from the neutral ones. Out of a pool of 260 nsSNPs, three SNPs (L56V, M176I, and C196R) been selected to anticipate their impacts on functions and structures along with their capability to impair protein stability. Actually, two of the three SNPs in the CRISP2 gene L56V and C196R were identified as possibly detrimental, although M176I was not. But all of these SNPs dropped significantly protein stability, per the I-Mutant suite.